Adhesion of osteoblasts to a nanorough titanium implant surface - Gongadze E (Dove Medical Press, 2011)
Ekaterina Gongadze1, Doron Kabaso2, Sebastian Bauer3, Tomaž Slivnik2, Patrik Schmuki3, Ursula van Rienen1, Aleš Iglič21Institute of General Electrical Engineering, University of Rostock, Rostock, Germany; 2Laboratory of Biophysics, Faculty of Electrical Engineering, University of Ljubljana, Ljubljana, Slovenia; 3Department of Materials Science, Friedrich-Alexander University of Erlangen-Nurenberg, Erlangen, GermanyAbstract: This work considers the adhesion of cells to a nanorough titanium implant surface with sharp edges. The basic assumption was that the attraction between the negatively charged titanium surface and a negatively charged osteoblast is mediated by charged proteins with a distinctive quadrupolar internal charge distribution. Similarly, cation-mediated attraction between fibronectin molecules and the titanium surface is expected to be more efficient for a high surface charge density, resulting in facilitated integrin mediated osteoblast adhesion. We suggest that osteoblasts are most strongly bound along the sharp convex edges or spikes of nanorough titanium surfaces where the magnitude of the negative surface charge density is the highest. It is therefore plausible that nanorough regions of titanium surfaces with sharp edges and spikes promote the adhesion of osteoblasts.Keywords: osteoblasts, nanostructures, adhesion, titanium implants, osteointegration